Development of mathematical model of fuzzy risk analysis in construction projects - Chaher, Zid (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
Construction projects are more subjective and risky compared to other projects due to the unique characteristics of construction activities and high level of uncertainty such as topographical factors of project, changing of weather, sort of project, the effects of economy, sub-contractor accessibility, and the impacts of politics, etc. Risk analysis and management of the project is the first key to achieve adequate level of project success. Previous few studies have been done to quantify risk analysis utilizing different methods, for example, Monte Carlo, Event Tree Analysis (ETA), Failure Mode and Effect Analysis, Risk Matrix. However, some of those methods are either limited and hard to be used or do not support the quantitative method because of the required measure of information to quantify and analyse the risk factors. Moreover, modern construction and new sophisticated design have shown significant obstacles and uncertainties to complete the project safely with success; thereby it is inevitable to search for a new approach to deal with uncertainties. The fuzzy system has the ability to convert the natural verbal human thoughts to computational comprehensive intervals, deliver the accurate reasoning process, and deal with inexact and vague information. Thus, this leads to an absolute result, fewer failures, and a lower tolerance for risk in construction projects. This research defines the critical factors in construction project success, namely the iron triangle time-cost-quality in the projects, reviews some techniques and methods in engineering construction projects, conducts an original contribution to develop a quantitative risk analysis method using fuzzy logic and validate the result in software Matlab. This research also describes the stages of the fuzzy risk analysis model which is developed to assess the risks related to construction projects and their uncertainties based on evaluations of the criteria of project success which represents the iron triangle: cost, time and quality. The method is verified on a real project which demonstrates the results of comparison and proves the advantages of using fuzzy logic as risk analysis method. Ultimately, by using this model we can prioritize and rank all risk factors cited in the construction project; besides that we can easily manage them in the best appropriate way. To sum up, using fuzzy risk analysis eases the risk of management process and affects positively the decision made by the experts to monitor and control the project and meet the satisfaction of stakeholders. As a result, the project will reach the ultimate degree of success.